THE DILEMMA OF STATE BUDGET POLICY: WHEN CENTRAL EFFICIENCY SACRIFICES VILLAGE FUNDS ( PHENOMENOLOGICAL STUDY IN RAINAWE VILLAGE, KOBALIMA DISTRICT, MALAKA REGENCY,EAST NUSA TENGGARA PROVINCE ) - Dominikus Isak Petrus Berek; Hendrik Toda; Melkisedek N B C Neolaka; Maria L Lino (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2026)
This study examines the dilemma of national budget policy affecting Village Funds in Malaka Regency, specifically in Rainawe Village, Kobalima District. Budget efficiency policies implemented by the central government through Presidential Instructions and related regulations have created tension between national fiscal interests and rural development needs. Using a phenomenological approach with in-depth interviews, observation, and budget document analysis, this study finds that: ( 1) village fiscal dependency reaches 99.2% of central transfers; ( 2) budget realization faces systemic barriers due to cuts and delayed transfers; ( 3) village officials experience alienation in top-down budgeting processes; and ( 4) village communities bear the direct impact of delayed development programs. This research concludes that efficiency policies that do not consider the context of remote villages will exacerbate development inequality between the center and regions.